Effect of Light Intensity to Chlorophyll and Anthocyanin Content in Mangosteen Leaf - Setiawan, Eko (Rekayasa, 2016)
The objective of this study was to understand the light intensity conditions of mangosteen trees to various branch position in canopy. The experiment was conducted using mangosteen trees grown on commercial orchard in Bogor, Indonesia during August - October 2013. Mangosteen trees of three different ages, young (20 years), middle (35 years), and old ages (50 years), each of five trees, are selected for study. Canopy of each tree divided into 9 sectors. The highest light intensity in full sunlight conditions was found in sector 9 were 8.07; 7.53; and 7.74 μ mol M-2 s-1, in young, middle and old age, respectively, in contrast, the lowest light intensity in sector 1 were 0.53; 0.42; and 0.49 μ mol M-2 s-1, in young, middle and old age, respectively. Chlorophyll a/b ratio in mangosteen leaves increase gradually as an increase of age, each in young, middle, and old age were 2.20; 2.25; and 2.95, respectively. The highest chlorophyll index was in branch with fruit production, than decrease in dormancy condition, whereas the lowest chlorophyll index in new flush or vegetative condition.